Effectiveness of Cognitive Behavioral Group Intervention on Body Image Improving and Increasing Self-Esteem in Women with Breast Cancer after Mastectomy - Ahmad Izadi-Ajirlo; Bahman Bahmani; Ali Ghanbari-Motlagh (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: This study was conducted to improve the body image and self-esteem among breast cancer patients after mastectomy. Materials & Methods: Our study comprised of 23 breast cancer patients in Imam Hossein Hospital, aged between 30-60 years, all of whom had undergone mastectomy and then radiotherapy. The study participants were selected through purposeful sampling and then randomly assigned to the case (10) and control (13) groups. The intervention program (cognitive behavioral group intervention) consisted of 12 sessions of intervention (2 sessions per week) each taking 90 minutes, in a 6 week process. Both group members completed the "body image and relationships scale" and the "Pope self- esteem questionnaire" before and after training. Analysis of covariance to eliminate the pretest effect on posttest results and ANOVA to determine the differences between the groups were used through SPSS 18 in this study. Results: This intervention was significantly effective on improving the mean score of body image and self- esteem in the breast cancer/mastectomy patients of the case group compared to that of the control group (P<0.01). Conclusion: Thus, cognitive behavioral group intervention can be effective in improving body image and increasing self-esteem among women with breast cancer after mastectomy.